Evaluating boron levels in Turkish mineral waters: a comparative study of three analytical techniques - YARAT, AYŞEN (My University, 2024)
Turkey is abundant in natural mineral water sources, thanks to its location on the Alpine-Himalayan belt. Natural mineral water is drinking water characterized by its natural mineral, trace elements, and carbon dioxide content. Because of quite insufficient data, the boron content in bottled natural mineral waters in Turkey was analyzed by three different methods and compared: inductively coupled plasma mass spectrometry technique, carminic acid, and azomethine-H methods, in this study. The boron levels in mineral waters ranged from a minimum of 0.05 mg/L to a maximum of 8.61 mg/L. It was also safe by the upper limit level estimated by the World Health Organisation. As boron plays a beneficial role in human physiology, consuming natural mineral water may offer a positive contribution to public health by supporting boron intake in our country. The other outcome of our research was that the spectrophotometric carminic acid method can yield results similar to those obtained using the inductively coupled plasma mass spectrometry technique since the boron level of Turkish mineral water was within the limits level of the carminic acid method. However, the result of the azomethine-H method was found not to be suitable. Cross-sensitivity with other elements in mineral water might have caused this.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Mühendislik; Sosyal Bilimler Genel; MÜHENDİSLİK, ÇEVRE; ÇEVRE ÇALIŞMALARI; Engineering, Computing & Technology (ENG); Social Sciences (SOC); ENGINEERING; SOCIAL SCIENCES, GENERAL; ENGINEERING, ENVIRONMENTAL; ENVIRONMENTAL STUDIES; Genel Mühendislik; Fizik Bilimleri; Kirlilik; Yönetim, İzleme, Politika ve Hukuk; General Engineering; Physical Sciences; Pollution; Management, Monitoring, Policy and Law; Azomethine-H; Boron; Carminic acid; ICP-MS; Natural mineral water